What Do (and Don't) We Know about the Value Added Tax? A Review of Richard M. Bird and Pierre-Pascal Gendron's The VAT in Developing and Transitional Countries - Keen, Michael (Journal of Economic Literature, 2009)
The VAT has taken the tax world by storm over the last fifty years, but left little trace in the academic literature. Bird and Gendron provide an impressively informed and informative account of the VAT experience in lower income countries, largely vindicating the tax and standard advice for its design. But they rightly stress too that dominant “expert opinion” on the VAT remains troublingly uninformed by serious analysis and evidence. This article focuses on some of these gaps and recent attempts to start filling them.